Dose dependency of outcomes of intrapleural fibrinolytic therapy in new rabbit empyema models - Komissarov, A; Florova, G; Azghani, A; Buchanan, A; Boren, J; Allen, T; Rahman, N; Koenig, K; Chamiso, M; Karandashova, S; Henry, J; Idell, S (American Physiological Society, 2016)
The incidence of empyema (EMP) is increasing worldwide, generally occurs with pleural loculation and impaired drainage is often treated with intrapleural fibrinolytic therapy (IPFT) or surgery. A number of IPFT options are used clinically with empiric dosing and variable outcomes in adults. To evaluate the mechanisms governing intrapleural fibrinolysis and disease outcomes, rabbit models of Pasteurella multocida and Streptococcus pneumoniae-induced EMP were generated. The animals were treated with either human tissue (tPA) plasminogen activator or prourokinase (scuPA). Rabbit EMP was characterized by the development of pleural adhesions detectable by chest ultrasonography and fibrinous coating of the pleura. Similar to human EMP, rabbits with EMP accumulated sizable; 20-40 ml fibrinopurulent pleural effusions associated with extensive intrapleural organization, significantly increased pleural thickness, suppression of fibrinolytic and plasminogen activating activities and accumulation of high levels of plasminogen activator inhibitor 1, plasminogen and extracellular DNA. IPFT with tPA (0.145 mg/kg) or scuPA (0.5 mg/kg) was ineffective in rabbit EMP (n=9 and 3 for P. multocida and S. pneumoniae, respectively). 2 mg/kg tPA or scuPA IPFT (n=5) effectively cleared S. pneumoniae-induced EMP collections in 24h with no bleeding observed. While intrapleural fibrinolytic activity for up to 40 min after IPFT was similar for effective and ineffective doses of fibrinolysin, it was lower for tPA compared to scuPA treatments. These results demonstrate the similarities between rabbit and human EMP, the importance of pleural fluid PAI-1 activity and levels of plasminogen in the regulation of intrapleural fibrinolysis and illustrate the dose dependency of IPFT outcomes in EMP.